Linear and whorled nevoid hypermelanosis with depigmentation - Preema Sinha; Manas Chatterjee; Kamlesh K Singh; Aradhana Sood (Wolters Kluwer Medknow Publications, 2017)
Linear and whorled nevoid hypermelanosis (LWNH) is a rare disorder of pigmentation characterized by hyperpigmented macules in a linear or whorled streaky configuration. Lesions are distributed mainly on the trunk and extremities, sparing the palms, soles, and mucosae. Depigmentation occurring in the pre-existing whorls has not been reported till date. Herein, we report one such rare case of familial LWNH with depigmentation.